1979
DOI: 10.1128/jb.137.2.977-989.1979
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of a duplicate antibiotic resistance gene and generation of deletions in plasmid R6K

Abstract: Transformation experiments showed that spontaneous deletions which result in loss of streptomvcin resistance and an increase in conjugal transfer efficiency are present at a frequency of about 10 4 in plasnid molecules of R6K. Similar deletions were thus readily selected by conjuLgal transfer of R6K, and their appearance was dependent upon lrecAactivity in either donor or recipient host. The deoxvribonucleic acid segment deleted in four mutants examined was concluded to extend from the same terminus of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
19
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…Chemicals and enzymes. In addition to those previously cited (21), the biochemicals used included: ATP (Sigma Chemical Co.); ampicillin trihydrate (Beecham Laboratories); bromophenol blue (Sigma); chloramphenicol (B grade, Calbiochem); dithiothreitol (Sigma); disodium EDTA and hydroxylamine sulfate (Eastman Kodak); 2-hydroxyethyl mercaptan (2-mercaptoethanol) and kanamycin (Sigma); methylene blue (Merck & Co., Inc.); mitomycin C (from Strepto-TABLE 1. Bacterial strainsa Genotype thr leu thi lac tonA supE44 (A-) (F-) his argG metB leu rpsL thy xyl lacYpolA (Ts) met bfe (A-) (F-) (R6K) thr leu thi lac thy tonA deoC rpsL (A-) (ColEl) C600 A trpE5 recA RC656 (R6K) RC62(pSJC102) RC656(pSJC102) RC656 cys(ColE2) ColE2 derivative of LT2 a Gene symbols used in this table and throughout the text are those recommended by Bachmann et al (3) and Novick et al (36).…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…Chemicals and enzymes. In addition to those previously cited (21), the biochemicals used included: ATP (Sigma Chemical Co.); ampicillin trihydrate (Beecham Laboratories); bromophenol blue (Sigma); chloramphenicol (B grade, Calbiochem); dithiothreitol (Sigma); disodium EDTA and hydroxylamine sulfate (Eastman Kodak); 2-hydroxyethyl mercaptan (2-mercaptoethanol) and kanamycin (Sigma); methylene blue (Merck & Co., Inc.); mitomycin C (from Strepto-TABLE 1. Bacterial strainsa Genotype thr leu thi lac tonA supE44 (A-) (F-) his argG metB leu rpsL thy xyl lacYpolA (Ts) met bfe (A-) (F-) (R6K) thr leu thi lac thy tonA deoC rpsL (A-) (ColEl) C600 A trpE5 recA RC656 (R6K) RC62(pSJC102) RC656(pSJC102) RC656 cys(ColE2) ColE2 derivative of LT2 a Gene symbols used in this table and throughout the text are those recommended by Bachmann et al (3) and Novick et al (36).…”
mentioning
confidence: 84%
“…R6K and the Tn3-carrying plasmid rSF1030 show an approximately 4-kb homology, inferred to be the ampicillin transposon (19). Previous experiments in this laboratory have shown that insertions of a duplicate Tn2660 element into R6K are found after selection of a recA + R6K host strain for increased resistance to ampicillin (21). These insertions appeared to be unstable in recA+ host strains and were frequently accompanied by deletions, but could be stabilized after transfer to a recA host.…”
mentioning
confidence: 93%
See 3 more Smart Citations